Writing and Reporting of Scalp Electroencephalography - Onur YILDIZ; Başak YILMAZ ÖZ; Seher Naz YENİ (Archives of Epilepsy, 2021)

(untitled)
Electroencephalography (EEG) is the gold standard for analyzing electrophysiological processes involved in epilepsy, as well as in several other dysfunctions of the central nervous system. Firstly, to properly interpret the EEG record, one must clearly have in mind the elements of a normal EEG. Secondly, to assist in producing useful information for clinical and research purposes, it is recommended to use standardized terminologies and to follow an orderly EEG reporting approach. The EEG report gives a clinical interpretation in light of the diagnosis and must meet the expectations of the clinician. The EEG terminology should be understandable to other physicians who are not specialized in EEG. The review aims to provide a standardized format for reporting the results of adult routine scalp EEG.